Buzzer Group Propaganda on Social Media (Case Study: Cyberwar Netizens about Lockdown Polemics/Quarantine Areas on Twitter Social Media) - Norvin Dwiyasa; Arthur Josias Simon Runturambi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Based on the latest data from the Covid-19 Task Force Team on March 30, 2020, there have been 1,414 cumulative positive cases, with 122 people dying, and 75 people being declared cured. Through the mapping of global coronavirus updates by John Hopkins University, the death rate for Covid-19 patients in Indonesia is highest in Southeast Asia and far surpasses neighboring countries. The increasingly widespread distribution causes high pressure from the public to immediately take extreme steps to prevent the spread from spreading further. Through the Twitter social media platform, there was a cyberwar between netizens to form arguments and discourses that could influence public opinion. Freedom of expression in the use of social media is used as a gap for buzzers to agitate and propaganda to win a cyberwar.